Large desmoid tumors in familial adenomatous polyposis - Vítor Devezas; Laura Elisabete Barbosa; Rosa Ramalho; Cristina Sarmento; José Costa Maia (University of São Paulo, 2018)
Desmoid tumors develop from connective tissue, fasciae, and aponeuroses, and may occur in the context of familial adenomatous polyposis or may arise sporadically; also, they may be extra-abdominal, intra-abdominal, or located in the abdominal wall. These benign tumors have a great aggressiveness with a high rate of local recurrence. Familial adenomatous polyposis is an inherited condition with autosomal dominant transmission, and is characterized by the development of multiple colonic and rectal adenomatous polyps, as well as desmoid tumors. We present the case of a 54-year-old woman with germline APC gene mutation, who underwent a total colectomy, subsequently developing two large infiltrative solid intra-abdominal lesions consistent with desmoid tumors. Medical treatment with Cox-2 inhibitors was initiated without result. She was submitted to resection for intestinal obstruction, but developed local recurrence. The lesions were also unresponsive to tamoxifen, and chemotherapy was initiated with dacarbazine plus doxorubicin, switching to vinorelbine plus methotrexate, achieving a good response in all lesions after 12 months. The approach to these intra-abdominal lesions should be progressive, beginning with observation, then a medical approach with non-steroidal anti-inflammatory drugs or with an anti-hormonal agent. Afterwards, if progression is still evident, chemotherapy should be started. Surgery should be reserved for resistance to medical treatment, in palliative situations, or for extra-abdominal or abdominal wall desmoids tumors.